Pengaruh Variasi Sudut Static Mixer Terhadap Kinerja Heat Exchanger - Widhiyanuriyawan, Denny; Purnami, Purnami; Ardiansyah, Ardiansyah (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2011)
This study was proposed to determine the effect of static mixer on innertube installation of double pipe heat exchanger. The dimenssion of outer (hot fluid) and inner (cold fluid) pipes of heat exchanger were 76.2 mm and 25.4 mm, respectively. Static mixers with 19 mm diameter and 60 pieces number were variated with Î¸=40o, 80o, and120o. The hot fluid discharges were variated from 400 to 900 liters/hour and the constant of cold fluid discharge with 900 liters/hour. The results show the heat transfer rate of statics mixer with angle variation higher than plain tube (without static mixer).The heat transfer increased 24%, 39%, and 44% for variation angel of static mixer with Î¸=40o, 80o, and 120o, respectivelly.Keywords: Static mixer, heat transfer rate